Ensino de ciências e meio ambiente: a concepção de alunos do Ensino Fundamental I sobre poluição do ar - CRUZ, Juliana Soares da (2020)
The air is a significant element of the environment, however, most of the population does not have an awareness of the existing issues surrounding air. This paper proposes to examine the conception that students of Elementary School I have about this pollution. The aim of this paper is to analyze how students relate air pollution to various problems caused in society, and how the use of Environmental Education can promote differentiated thoughts from its application in the classroom. The work was carried out at a public school in Belém, and the participants were 23 students from the 3rd year of elementary school. The research is based on a qualitative research and how methodology was used science wheel, music use and clothesline drawings. For the investigation of the results the Discursive Textual Analysis (ATD) was used. From the results it can be inferred that students understand about air pollution, and after class there was a better understanding about the concepts addressed.